NEUROLOGICAL MUSIC THERAPY (NMT) IN AUTISM SPECTRUM DISORDER (ASD): EVIDENCE, INTERVENTIONS, AND MEASURABLE CLINICAL POSSIBILITIES FOR BRAZIL - Narthagnan Chaves da Silva, Francisco (Health and Society, 2025)
Autistic Spectrum Disorder (ASD) involves persistent changes in communication, social interaction and restricted and repetitive patterns of behavior. Neurological Music Therapy (Neurologic Music Therapy - NMT) is an international therapeutic model based on neuroscience, composed of 20 standardized techniques that allow measurable interventions in the motor, linguistic and cognitive domains. This article deepens the neurobiological mechanisms underlying the NMT and discusses its applications in ASD, gathering recent scientific evidence that points to gains in motor coordination, attention, engagement and functional communication. Internationally, NMT is recognized as evidence-based practice and used in rehabilitation centers in Canada, the United States and Europe. In Brazil, however, its diffusion is still limited. Based on the experience of the author - neuropsychologist, neurotherapist, behavioral analyst, member of the World Federation for NeuroRehabilitation (WFNR), autistic individual and father of autistic children - this work proposes the NMT as a valid, safe and necessary tool in the field of neurorehabilitation and autism.